Effects of Pediococcus pentosaceus PKWA-1 and Bacillus subtilis BA04 on Growth Performances, Immune Responses and Disease Resistance against Aeromonas hydrophila in Nile Tilapia (Oreochromis niloticus Linn.) - Saichai Kaew-on (Science Faculty of Chiang Mai University, 2019)
Probiotics are beneficent dietary supplements in aquaculture. The aim of this study was to evaluate the effects of Pediococcus pentosaceus PKWA-1 and Bacillus subtilis BA04 on growth performances, immune responses and survival after challenge with Aeromonas hydrophila of Nile tilapia. The tilapia fish were fed with four different diets: basal diet (G1) or diet supplemented with 1 ´ 107 CFU/g PKWA-1 (G2); 1 ´ 107 CFU/g BA04 (G3); or with the mixture of 0.5 ´ 107 CFU/g PKWA-1 and 0.5 ´ 107 CFU/g BA04 (G4) at the rate of 5% of body weight, twice a day. After 42 days of feeding, G2, G3 and G4 showed no significant different improvement daily weight gain and specific growth rate compared with G1 (P > 0.05). After 14 days, the immune responses showed significant enhancements of phagocytic activity and alternative complement activity in G2, G3 and G4. Significant enhancement of serum lysozyme activity was found after 28 days of feeding within such groups. Interestingly, G4 showed persistent enhancement in alternative complementary activity and serum lysozyme activity. No significant difference of total leucocyte count was found between the supplemented and control groups. After 30 days, G2, G3 and G4 showed disease resistance against Aeromonas hydrophila. The relative percentage survival ranged from 22.5% to 27.5% in G2, G3, G4 and 0% in G1. These results suggest that the use of PKWA-1 and BA04 single or in combination as feed supplements is beneficial to Oreochromis niloticus.